Pengaruh Perkembangan Teknologi Terhadap Kehidupan Sosial Remaja - Widdya Rahmalina; Wita Yulianti (Akademi Farmasi YPPM Mandiri, 2022)
Technological developments at any time will continue to develop advanced technological tools are now technologically very sophisticated and facilitate human work or can do human work. The development of technology that is getting more advanced and sophisticated at any time ensures that technology has both advantages and disadvantages. One of the technological developments that are currently being advanced is the smartphone. The development of this smartphone, development is more dominant among teenagers. Adolescent level is a level that has an ego that is still unstable or has not been controlled. Adolescence is a period that does not know the direction of their goals in treading life. The development of technology that has entered the world of teenagers is very influential in their lives, especially the social life of teenagers. Adolescents are included in the middle or high school group. They must know the influence of technological developments, namely the positive and negative impacts. By providing knowledge about technological developments and their impacts, adolescents can sort and choose what is good and bad for themselves and are given examples of the results of technological developments in the form of smartphones visually.